Radiographic Assessment of the Hind Limb Bone Development in Maned Wolves (Chrysocyon brachyurus) - Gonçalves, Raphael A. B. [UNESP]; Rahal, Sheila C. [UNESP]; Silva, Jeana P. [UNESP]; Cassanego, Guilherme R. [UNESP]; Mamprim, Maria J. [UNESP]; Rolim, Luna S. [UNESP]; Teixeira, Carlos R. [UNESP]; Inamassu, Letícia R. [UNESP] (Wiley, 2025)
This study aimed to analyse the growth plate fusion and secondary ossification centres of the hind limbs in maned wolves (Chrysocyon brachyurus) using radiographs. Data from three maned wolves estimated to be 3–4 months old were utilised. The right and left hind limbs were radiographed in the mediolateral and craniocaudal views once a month until 11–12 months of age and then every 2–3 months until 18–19 months of age. The growth plates identified in the hind limbs and their closure times were as follows: proximal femur (13–15 months), distal femur (13–15 months), proximal tibia (17–19 months), tibial tuberosity (17–19 months), distal tibia (11–13 months), proximal fibula (13–15 months) and calcaneal tuber (8–9 months). Measurements of the areas of the secondary ossification centres of the proximal epiphysis of the femur, distal epiphysis of the tibia, patella and fibular tarsal bone epiphysis showed a significant difference between the first assessment and 6–7 months. The distal femoral epiphysis, proximal tibial epiphysis and tibial tuberosity showed a statistically significant difference between the first assessment and 7–8 months. The difference in the proximal epiphysis of the fibula was observed between 4 to 5 months and 7 to 8 months. In conclusion, the information obtained regarding the growth plates and secondary ossification centres of the maned wolves may support other studies and help understand the normal patterns of the species.
Keywords: epiphysis; growth plates; wild animal